Insights into quorum sensing (QS): QS-regulated biofilm and inhibitors - Wen-Si Tan; Jodi Woan-Fei Law; Lydia Ngiik-Shiew Law; Vengadesh Letchumanan; Kok-Gan Chan (Progress in Microbes and Molecular Biology)
In the environment, bacteria can communicate with a known mechanism called quorum sensing (QS). These bacteria will communicate in a group for social interactions like a multi-cellular organism. It provides significant benefits to the bacteria in host colonization, the formation of biofilms, defense against competitors, and adaptation to environmental changes. The bacteria that organize in biofilms are difficult to control and manage, resulting in a higher dosage of antibiotics to clear the infectious biofilms. Also, many QS-controlled activities are involved in virulence and pathogenicity. Hence, understanding the details of quorum sensing mechanisms, its phenotype regulation (biofilm), and QS inhibitors (which attenuate virulence/pathogenicity) may open a new avenue for controlling bacterial infections.